Relationship between General and Spinal Anesthesia and Its Impact upon Breast Feeding: Comparative Study - humadi, Zainab; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2016)
Objective: To identified the relationship between general and spinal Anesthesia upon breastfeeding and (demographic &reproductive) : Comparative Study. Methodology: The present study employs a descriptive comparative design held at the labor and delivery room , operational room for cesarean section and maternity word in maternity department at Al Emamain Al Kadhamain Medical City in Baghdad city. Data collection was initiated on 2nd January to end of March /2014. Purposive sample consisted of (150) mother and her neonate, The study sample divided into three groups:(50) under general anesthesia , (50) under spinal anesthesia ,(50) normal vaginal delivery and considered control group. An assessment tool was constructed for the purpose of the study, it was comprised of socio-demographic data, mother reproductive history, information about neonate age, weight, Apgar score, anesthesia effect on neonate after delivery and assessment of breast feeding immediately after birth and anesthesia effect on bonding. Results : The main results of the study shows that the highest percentage of neonate age at ( 1 & 2) hours after delivery, , Neonate weight 3000 gm., general group had illustrated low Apgar scoring scale comparing with others groups. Mother choice of anesthesia, odds ratio indicator showed that choice of general anesthesia twice times of choice spinal anesthesia .Regarding mother practice of breast feeding, mother in general anesthesia started breastfeeding after two attempts or more ,while in N.V.D. started from first attempt, for the reasons of inability to achieve breast feeding, all items in general reported failure assessment, also in and spinal groups all items reported failure except in Feeling severe pain after the operation", " The mother in recovery room immediately after the operation", and "Lack of milk flow as a result of anesthesia" which reported pass assessment. Finally, N.V.D. has reported pass assessment in light of preceding part. Reasons related to child", general and spinal groups are reported failure assessments in light of "A child needs to transfer to the intensive care unit, and Baby feeling tired and not being able to breast feeding" items, and the leftover items are reported pass assessments. While, N.V.D. has reported pass assessment in all items. Effectiveness of anesthesia on breastfeeding shows failure assessment in general and spinal group in mother practice , reasons related to mother and newborn, while pass in N.V.D. group. Regarding mother-neonate bonding ,results of effectiveness shows failure assessment in general and pass in spinal and N.V.D. group.. Recommendations: Early mother-neonate bonding appears to offer some clinical benefit, particularly for breastfeeding. Supportive policies are needed in hospitals and birthing centers to help implement this intervention, which might be regarded as "natural".